Multi-Planar Cervical Motion Dataset: IMU Measurements and Goniometer - Lee Keidan; Rawan Ibrahim; Evyatar Ohayon; Chaim G. Pick; Ella Been (Scientific Data)
Abstract This data descriptor presents a comprehensive and replicable dataset and method for calculating the cervical range of motion (CROM) utilizing quaternion-based orientation analysis from Delsys inertial measurement unit (IMU) sensors. This study was conducted with 14 participants and analyzed 504 cervical movements in the Sagittal, Frontal and Horizontal planes. Validated against a Universal Goniometer and tested for reliability and reproducibility. Analysis showed strong validity in the sagittal plane (R = 0.828 ± 0.051) and moderate in the frontal (R = 0.573 ± 0.138), with limitations in the horizontal plane (R = 0.353 ± 0.122). Reliability was high across all planes (Sagittal: ICC = 0.855 ± 0.065, Frontal: ICC = 0.855 ± 0.015, Horizontal: ICC = 0.945 ± 0.005). Our model for CROM measurements is a valuable tool aiding diagnosis, treatment planning, and monitoring of cervical spine conditions. This study presents an accessible analysis process for biomechanical assessments in cervical and spinal fields. The dataset herein serves as a benchmark for state-of-the-art machine learning models predicting head/neck position, analyzing smoothness of movements, measuring standard motion patterns, and calibrating drift based on movement comparisons.